PETROLIFEROUS STRATA OF CONTINENTAL-MARGIN BASINS - Geodekyan A.A.; Zabanbark A.; Konyukhov A.I. (My University, 1989)
Widespread exploration and test drilling in basins located on continental margins, chiefly on coastal plains and shelf, has revealed numerous oil and gas pools, which, as shown by analysis of geophysical data and well cores, are distributed very unevenly in the section and are concentrated mainly in sedimentary complexes of certain composition and genesis. After studying and summarizing all available relevant information in the literature, we compiled two tables that may shed some light on the problem of the composition and the genesis of deposits in which oil and gas pools are concentrated on continental margins. We distinguished very broad groups of sediments: continental, deltaic, shallow-water marine and deep-sea for clastic strata, as well as reef limestones and limestones of other origin plus dolomites for carbonate varieties. Here, too, we separately considered siliceous deposits, tuffs, tuffaceous sandstones and quartzites. These tables give some idea of the relative importance of various sedimentary complexes as oil and gas reservoirs on tectonically active and passive continental margins.